Does Mining FDI Crowd in Other Investments? Investigation of FDI Intersectoral Linkages - Doytch, Nadia (Archīum Ateneo, 2015)
This paper analyzes whether mining FDI ‘crowds in’ or ‘out’ FDI in other sectors via intersectoral linkages. It utilizes a novel data set covering an unbalanced panel of sector-disaggregated FDI flows for 70 countries during the period from 1985 to 2010. Results show differential effects of mining FDI on FDI in other sectors (manufacturing, financial services, non-financial services) and across country groups. Some of the most interesting results are seen in the high-income countries group, where mining FDI is observed to have a crowding-out effect on financial services FDI, and in the lower middle-income countries group, where mining FDI is observed to crowd in both manufacturing and financial services FDI.